End-to-end Mars entry, descent, and landing modeling and simulations for Tianwen-1 guidance, navigation, and control system - Xu, Chao; Huang, Xiangyu; Guo, Minwen; Li, Maodeng; Hu, Jinchang; Wang, Xiaolei (Astrodynamics, 2022)
On May 15, 2021, the Tianwen-1 lander successfully touched down on the surface of Mars. To ensure the success of the landing mission, an end-to-end Mars entry, descent, and landing (EDL) simulator is developed to assess the guidance, navigation, and control (GNC) system performance, and determine the critical operation and lander parameters. The high-fidelity models of the Mars atmosphere, parachute, and lander system that are incorporated into the simulator are described. Using the developed simulator, simulations of the Tianwen-1 lander EDL are performed. The results indicate that the simulator is valid, and the GNC system of the Tianwen-1 lander exhibits excellent performance.